2015
DOI: 10.1038/srep10547
|View full text |Cite
|
Sign up to set email alerts
|

Spin-dependent Seebeck Effect, Thermal Colossal Magnetoresistance and Negative Differential Thermoelectric Resistance in Zigzag Silicene Nanoribbon Heterojunciton

Abstract: Spin-dependent Seebeck effect (SDSE) is one of hot topics in spin caloritronics, which examine the relationships between spin and heat transport in materials. Meanwhile, it is still a huge challenge to obtain thermally induced spin current nearly without thermal electron current. Here, we construct a hydrogen-terminated zigzag silicene nanoribbon heterojunction, and find that by applying a temperature difference between the source and the drain, spin-up and spin-down currents are generated and flow in opposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“… 25 , but here extended from collinear magnetic alignment and including a computation of the spin Seebeck effect. The thermal generation of a spin current and an associated spin voltage is known as the spin 47 or spin-dependent 48 Seebeck effect (we will stick with the former notation in this manuscript). Within the quasiclassical approximation, only particles with energies close to the Fermi surface are assumed to contribute to transport, and the Green function matrices are nearly isotropic with respect to momentum 49 .…”
mentioning
confidence: 99%
“… 25 , but here extended from collinear magnetic alignment and including a computation of the spin Seebeck effect. The thermal generation of a spin current and an associated spin voltage is known as the spin 47 or spin-dependent 48 Seebeck effect (we will stick with the former notation in this manuscript). Within the quasiclassical approximation, only particles with energies close to the Fermi surface are assumed to contribute to transport, and the Green function matrices are nearly isotropic with respect to momentum 49 .…”
mentioning
confidence: 99%
“…Dirac-like electron dispersion, 14,15 extremely high carrier mobility, 16 spin Hall effect, 17 and spin Seebeck effect, 18 but also some superior features, such as large spin filter effect. 19 large spin-orbital coupling, 22 which is important for achieving topological insulating states.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that increasing the width of armchair applying temperature difference between source and drain results in oppositely flowing spin-up and spin-down currents indicating thermal spin currents in zigzag SiNRs. 109 Creating opposite spin currents reduces the conducting electron current in the material and thus, the related Joule heating is much suppressed which indicates potential applications of zigzag SiNRs in low-power-consumption technology. An et al studied spin-polarized currents in SiNRs by applying local exchange field and reported that upon applying a weak local exchange field parallel to the surface of SiNRs on one of the edges of the NR, a gap is induced in the corresponding edge states while another pair of gapless edge states with opposite spin are still protected by time-reversal symmetry.…”
Section: A Gnrs' Cousin: Silicene Nrsmentioning
confidence: 99%